AI HAKIM: MEREVOLUSI PERADILAN YANG BERINTEGRITAS, BERMARTABAT, DAN MENINGKATKAN KESEJAHTERAAN HAKIM - Zico Junius Fernando (Ikatan Hakim Indonesia (IKAHI), 2024)
The development of Artificial Intelligence (AI) has offered transformative opportunities in various sectors, including the justice system. In the Indonesian context, the implementation of AI as a judge promises the potential to address the integrity and efficiency challenges faced by the judicial system, which has been tainted by cases of corruption and susceptibility to subjective bias. By leveraging AI's ability to process big data quickly and objectively, it is expected to create a more transparent decision-making process, reduce bias, and minimise the potential for corruption. This research discusses the implementation of AI in the role of a judge in Indonesia's criminal justice system, examines the potential efficiency, objectivity, and transparency offered by AI, and explores the synergy between AI and human judges in improving the quality of legal services. Through theoretical analysis, this research highlights the importance of standards and protocol development, transparency, training and education, and regular evaluation in AI integration. Cooperation between AI and human judges not only enriches the decision-making process in the judiciary but also maintains the humanistic core of law. This research shows that with a careful and ethical approach, the integration of AI in the justice system can strengthen fairness, improve efficiency, and ensure that technology supports, not replaces, the discretion of human judges, opening a new era in a fairer, more efficient, and dignified judiciary. Translated with DeepL.com (free version)